In the 1st video of integration by parts in question [xcos inverse 1] /[under root(1-x*x)] after solving, how sint become [under root(1-x*x)]

Asked by Subha Maiti | 19th Jul, 2013, 03:10: PM

Expert Answer:

We substituted cos-1x = t
=> cos t = x
=> cos2t = x2                [By squaring both sides]
=> 1 - sin2t = x2           [Using identity sin2t + cos2t = 1]
=> 1 - x2 = sin2t
=> sint = root (1 - x2)

Answered by  | 21st Jul, 2013, 12:56: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.